Case report: Interdisciplinary treatment of complex C1/C2 fractures in a patient with concomitant three-vessel coronary artery disease requiring bypass surgery - Di Francesco, M. E.; Magunia, H.; Örgel, A.; Tatagiba, M.; Radwan, M.; Adib, S. D. (Frontiers in Surgery, 2023)
Background: Acute myocardial infarction (MI) frequently leads to consciousness disturbance following hemodynamic collapse. Therefore, MI can occur together with upper cervical spine trauma. Herein, we report the successful treatment of complex C1/C2 fractures in a patient with concomitant three-vessel coronary artery disease (CAD). Case presentation: A 70-year-old patient presented in our emergency outpatient clinic after a hemodynamic collapse without neurological deficits or heart-related complaints. Computed tomography (CT) scan of the cervical spine revealed a dislocated odontoid fracture Anderson and D’Alonzo type II and an unstable Gehweiler type III injury (Jefferson’s fracture). An intradiploic arachnoid cyst in the posterior wall of the posterior fossa was a coincident radiological finding. Furthermore, coronary angiography confirmed three-vessel CAD with high-grade coronary artery stenosis. Indication for upper cervical spine surgery and bypass surgery was given. An interdisciplinary team of neurosurgeons, cardiothoracic surgeons and anesthesiologists evaluated the patient's case to develop the most suitable therapy concept and alternative strategies. Finally, in first step, C1-C2 fusion was performed by Harms technique under general anesthesia with x-ray guidance, spinal neuronavigation, Doppler ultrasound and cardiopulmonary monitoring. Cardiothoracic surgeons were on standby. One month later bypass surgery was performed uneventfully. Follow-up CT scan of cervical spine revealed intraosseous screw positioning and beginning fusion of the fractures. The patient did not develop neurological deficits and recovered completely from both surgeries. Conclusions: Treating complex C1/C2 fractures with concomitant severe CAD requiring treatment is challenging and carries a high risk of complications. To our knowledge, the literature does not provide any guidelines regarding therapy of this constellation. To receive upper cervical spine stability and to prevent both, spinal cord injury and cardiovascular complications, an individual approach is required. Interdisciplinary cooperation to determine optimal therapeutic algorithms is needed.